"Everyone has their own problems and realities so the religious community cannot judge someone." Contraception motivations and perceived consequences among young contraceptive users who practice a religion in Burkina Faso - Fiacre Bazié; Ilene S. Speizer; Amelia Maytan-Joneydi; Kindo Boukary; Moh Fatimata Troaré; Balki Ibrahim Agali; Yentema Onadja; Georges Guiella (BMC, 2024)
Abstract Background Numerous factors at the individual, interpersonal, and societal levels are related to contraceptive use (or non-use) among adolescents and youth. Little is known about the role of religion as an individual and community-level influencer of contraceptive use among young women. Methods Using in-depth interviews with 24 young contraceptive users ages 18-24 who practice their Catholic, Protestant or Muslim religion in two cities in Burkina Faso, this study examines motivations and perceived consequences of contraceptive use. By including users of modern contraception who were both single and married, a range of perspectives are provided. Results Generally, the young women interviewed who practice their religion and use contraception perceived that their religion was not supportive of contraceptive use. A few exceptions were provided, including perceived acceptance of use of some methods for married women for spacing purposes; this was specifically identified as acceptable among Muslim respondents. Sexual activity and contraceptive use were not acceptable by any of the religions for unmarried young women. That said, young women, both married and unmarried, reported their motivations for use that often related to their and their children's health and the realities of life. Contraceptive use was considered a private matter which meant that the religious community would not find out about women's use. Conclusions Recognizing that some women are willing and able to use contraception even without the perceived support of their religious communities might help to push social norms to change and be more accepting of contraceptive use that meets young women's and families' circumstances.